Land, Water, Mathematics, and Relationships: What Does Creating Decolonizing and Indigenous Curricula Ask of Us?. Issue 3 (4th May 2021) - Kulago, Hollie A.; Wapeemukwa, Wayne; Guernsey, Paul J.; Black, Matthew
Abstract: Indigenous epistemologies view a person as a whole, interconnected to land, in relationship to others. Knowledge is subjective and collective. However, hegemonic western knowledge created dualism that are perpetuated through western schooling with detrimental effects on Indigenous knowledge systems and livelihood. The dualisms separate mind from body, body from nature, and spirit from matter which led to western schooling practices that support goals of settler colonialism including dispossession of Indigenous peoples from their lands. This article presents theoretical and conceptual discussions, personal reflections, and relationship-building the authors engaged while creating decolonizing and Indigenous syllabi in the fields of environmental studies, philosophy, and mathematics education at the university level. Engaging these processes disrupts the separation created through western dualisms and move toward reconnection as an initial step in creating decolonizing curricula, shifting dominant curricula organized through the logics of settler colonialism, to curricula that envision and support Indigenous nations and sovereignty.